Pengaruh Kinerja Keuangan Daerah Terhadap Kesejahteraan Masyarakat di Kabupaten/Kota Se-Provinsi Kalimantan Tengah Tahun 2020 dan 2021 - Honggara, Albert; Jamaluddin, Jamaluddin (Universitas Muhammadiyah Gresik, 2024)
This research aims to determine the influence of regional financial performance on community welfare in districts/cities in Central Kalimantan Province. Regional financial performance is measured by the regional financial independence ratio and the effectiveness ratio of Regional Original Income, while community welfare is measured by the Human Development Index (HDI). This research was conducted in 14 districts/cities in Central Kalimantan Province. The research method used in this research is multiple linear regression. The analytical tool used is the Statistical Program for Social Science. The type of data used in this research is secondary data. The data used in this research is the realization of regional income and expenditure budgets from 2020-2021. Realization of regional income and expenditure budgets is obtained through the website of the Directorate General of Regional Financial Balance. HDI data is obtained through the Central Statistics Agency website. The results of this research show that the regional financial independence ratio has a partial effect on community welfare, while the regional original income effectiveness ratio has no partial effect on community welfare in all regencies/cities in Central Kalimantan Province.